2007
DOI: 10.1111/j.1746-1561.2007.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Performance and Substance Use: Findings From a State Survey of Public High School Students

Abstract: The present findings highlight the extensive use of cigarettes, alcohol, and marijuana among Mississippi public high school students. Because poor academic achievers are more prevalent among students who participate in these substance-use behaviors, multifaceted approaches that encourage high levels of academic performance, while dissuading student involvement in risky/problem behaviors, may both improve low levels of academic achievement and reduce behaviors that contribute to poor health in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
156
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(183 citation statements)
references
References 21 publications
24
156
1
2
Order By: Relevance
“…Given the association between substance use and depression, suicide, violence, fatal car accidents, academic problems, and the development of SUDs 2, 6,8,12,39 and the potential effectiveness of brief interventions and treatment of substanceinvolved adolescents, 40,41 it is of considerable importance that pediatricians, family physicians, and other health care providers screen adolescents for substance use. The use of the BSTAD or similar instruments can be an important step in identifying substance use and successfully intervening in the lives of adolescent patients.…”
Section: Discussionmentioning
confidence: 99%
“…Given the association between substance use and depression, suicide, violence, fatal car accidents, academic problems, and the development of SUDs 2, 6,8,12,39 and the potential effectiveness of brief interventions and treatment of substanceinvolved adolescents, 40,41 it is of considerable importance that pediatricians, family physicians, and other health care providers screen adolescents for substance use. The use of the BSTAD or similar instruments can be an important step in identifying substance use and successfully intervening in the lives of adolescent patients.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents who smoke very often are more likely to have low grades compared to their peers who do not smoke (Cox, Zhang, Johnson, & Bender, 2007;Diego, Field, & Sanders, 2003). Furthermore, MacLellan, Taylor, and Wood (2008) found that adolescents who reported better academic performance were also more likely to have a healthier diet.…”
Section: Health and Academic Successmentioning
confidence: 99%
“…Various aspects of health impact on the academic success of adolescents, including negative mood, feelings of low self-esteem and depression (DeSocio & Hootman, 2004) Adolescents who smoke very often are more likely to have low grades compared to their peers who do not smoke (Cox, Zhang, Johnson, & Bender, 2007;Diego, Field, & Sanders, 2003). Furthermore, MacLellan, Taylor, and Wood (2008) found that adolescents who reported better academic performance were also more likely to have a healthier diet.…”
Section: Health and Academic Successmentioning
confidence: 99%
“…Regarding academics, juveniles who are involved with substance use/abuse are more susceptible to declining grades, absenteeism from school and extracurricular activities, and have a higher rate of dropping out of school (Williams, Davis, Johnson, Williams, Saunders and Nebbitt, 2007). Cox, Zhang, Johnson, and Bender (2007) reported that there is a complex relationship between substance use/abuse and academic performance.…”
Section: Life Areas Affectedmentioning
confidence: 99%
“…This will contribute to poor academic performances for the juveniles and a disruption in learning for their classmates. One way in which educators and administrators can begin to address this problem is to encourage juveniles' involvement in afterschool activities and/or programs, provide additional learning resources such as tutoring or peer mentoring, and advocate for additional community resources for juveniles and their families (Cox, Zhang, Johnson, & Bender, 2007).…”
Section: At the Mezzo Levelmentioning
confidence: 99%